2020
DOI: 10.1063/5.0019488
|View full text |Cite
|
Sign up to set email alerts
|

Domain engineering in LiNbO3 crystals by e-beam and features of spatial distribution of electric field: Experiment and computer simulation

Abstract: Domain gratings with different periods were formed on −Z surfaces of lithium niobate using direct electron beam writing (DEBW) at an accelerating voltage of 15 kV. Features of the gratings obtained were compared to computer simulation results of spatial distribution of an electric field for various schemes of e-beam charges disposed near the sample surface. The Monte Carlo method was used to calculate the injection charge distribution. The electrical potential distribution in irradiated samples was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The opposite +Z surface of the thick samples (∼500 µm) was grounded by a deposited layer of aluminum. In DEBW, irradiated square arrays like those in [29] were used. The squares were placed on the nodes of the grid whose lines were parallel to the chosen orthogonal crystallographic axes X and Y on the cut −Z of LN.…”
Section: Samples and Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The opposite +Z surface of the thick samples (∼500 µm) was grounded by a deposited layer of aluminum. In DEBW, irradiated square arrays like those in [29] were used. The squares were placed on the nodes of the grid whose lines were parallel to the chosen orthogonal crystallographic axes X and Y on the cut −Z of LN.…”
Section: Samples and Methodsmentioning
confidence: 99%
“…The selection of H x parameter values for S1 and S2 is based on the results of [29], where it was shown that in the selected DEBW scheme at 15 kV the value of this parameter equal to 3 µm is the threshold proximity of injected charges, at which point regular periodically poled LN structures are still formed.…”
Section: Samples and Methodsmentioning
confidence: 99%
See 3 more Smart Citations